PENGARUH KETINGGIAN PERMUKAAN LAUT (DPL) TERHADAP KESTABILAN SUHU DAN KELEMBAPAN KOLAM IKAN AIR TAWAR SEBAGAI SUMBER BELAJAR - Sodiq, Nur Ali; Suseno, Nyoto; Prihandono, Eko (JURNAL FIRNAS, 2022)
Abstract: This research is aimed to determine the stability of temperature and humidity between fish ponds in the lowlands and highlands. This study aims to investigate (1) the effect of sea level in a specific area towards the stability of temperature and humidity of freshwater fish ponds. (2) the relationship between sea level and temperature as well as humidity of fish ponds. The research results from the effect of sea level (asl) on the stability of temperature and humidity of freshwater fish ponds is composed in the form of book for learning resources. This type of research as experimental research and this study used two ponds for data collection, namely ponds in the lowlands and highlands. The tools used in this research were thermometer, hygrometer and altimeter. Research in the lowlands in the village of Pekalongan, Pekalongan Regency is 50 meters above sea level and the highlands in the village of Alert, Sekincau Regency is 1,142 meters above sea level. The result of the stability of the lowland fish pond temperature was between 27.1–33.0ºC, the highland fish pond temperature was between 21.6–25.9ºC. The stability of the lowlands fish pond humidity was between 38–87%, the highland fish pond humidity is 21-84%. The Differences in temperature and humidity stability occur in fish ponds in the lowlands and fish ponds in the highlands, therefore the temperature and humidity of lowland fish ponds are more ideal than highland fish ponds. The movement of fish in lowland ponds is quite fast and often moves. The movement of fish in upland ponds is slow and fish often rise to the surface of the water in search of oxygen.Keywords : Lowlands Fishpond, Highland Fishpond, Temperature, Humidity